OneHealth Approaches Contribute Towards Antimicrobial Resistance: Malaysian Perspective - Mariappan, Vanitha; Vellasamy, Kumutha Malar; Mohamad, Nor Alia; Subramaniam, Sreeramanan; Vadivelu, Jamuna (Frontiers in Microbiology, 2021)
On a global scale, antimicrobial resistance (AMR) is recognized as a One-Health challenge due to the continual and increased development and distribution of resistant microbes and genes among humans, animals, and the environment. These sectors contribute to the increase of AMR, as antibiotics are widely used in healthcare, as growth enhancers metaphylactics in animal husbandry, and transmitted in the environment through irrigation using wastewater. However, there is a major drawback in terms of the lack of research assessing the coexistence of AMR in these sectors. Extensive research highlighted food-animal manufacture structures that are in the cards to harbour reservoirs or promote transmission of AMR, in addition to increasing human colonisation with AMR commensal bacteria. Numerous Antibiotic Stewardship policies designed and implemented in medical practices and farms in high- and middle-income countries. However, research concentrating on high-income-settings, attitudes, emotions, and beliefs on the utilisation of antimicrobials remain underexplored in lower- and middle-income countries such as Malaysia. Microbiological, epidemiological, and social science exploration are required at community and farming across the One-Health range to fill huge gaps in information and knowledge of AMR. Manipulating human activities and character associated with antibiotics is a multifaceted progression that includes elements like knowledge, social behaviour, attitudes, approaches, social standards, socio-economic settings, peer-pressure, experiences, and biophysical environment. Therefore, understanding these aspects in the utilisation of antimicrobial drugs among the different sectors is essential to develop and implement policies to curb AMR development and transmission that cut across all sectors within the One-Health consortium in Malaysia.